2017
DOI: 10.1111/ijag.12331
|View full text |Cite
|
Sign up to set email alerts
|

Ag/M‐seed/AZO/glass structures for low‐E glass: Effects of metal seeds

Abstract: In this work, continuous and conductive ultrathin Ag films with highly infrared reflective and highly visible transmittance were achieved using several metal seeds (Ti, Nb, Cr, Ni, Mo, Pt, Cu, and Ru), having ~1‐2 nm in thickness, deposited between Ag and dielectric AZO layers on glass substrate by magnetron sputtering with confocal target geometry. The optical properties in the visible and infrared ranges and conductivity of Ag/M‐seed/AZO/glass structures were compared in order to determine the influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Ultrathin metal films (UTMFs) are of high technological interest in optoelectronics, as they are widely employed in many applications, such as transparent conductors , photovoltaics, low emissivity windows, infrared absorbers, plasmonic metasurfaces, and point-of-care biosensors, to name a few. Interestingly, it was shown theoretically and experimentally that UTMFs of noble elements such as Ag and Au with a sufficiently low nanometric thickness can support two-dimensional-like plasmons with optical tunability by electrical gating. , UTMFs of Ag and Au can be grown in a crystalline form on silicon templates, with plasmons demonstrated in atomically thin silver films .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrathin metal films (UTMFs) are of high technological interest in optoelectronics, as they are widely employed in many applications, such as transparent conductors , photovoltaics, low emissivity windows, infrared absorbers, plasmonic metasurfaces, and point-of-care biosensors, to name a few. Interestingly, it was shown theoretically and experimentally that UTMFs of noble elements such as Ag and Au with a sufficiently low nanometric thickness can support two-dimensional-like plasmons with optical tunability by electrical gating. , UTMFs of Ag and Au can be grown in a crystalline form on silicon templates, with plasmons demonstrated in atomically thin silver films .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the addition of an ultrathin seed layer on the dielectric substrate can dramatically change the surface wetting properties and the subsequent growth of Ag and Au UTMFs, promoting their percolation at much smaller thicknesses. For example, it has been demonstrated that metallic seed layers of Al, Cr, Ti, , Au, and Cu could reduce the percolation thickness to about 3 nm. More recently, the percolation thickness was further reduced and continuous films were obtained when a Cu seed layer was exposed to ambient air before the Au UTMF deposition. , Highly percolating Cu and Ag UTMFs were also obtained with seed layers of Cu and Ag, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the reduction of energetic costs is a global issue in many areas. In the field of building construction or car production, the development of low-emissivity (low-e) glasses that reflect infrared ( i.e ., heat) and ultraviolet light is a major path to control heating and improve comfort in habitable spaces. , Low-e glasses rely on multilayered architectures incorporating silver in contact with various metal oxides (typically ZnO, TiO 2 , SnO 2 ). Among all of these oxides, zirconia (ZrO 2 ) is another material of interest that is widely used in a large range of technical and biomedical applications due to its good mechanical properties, in particular its high strength and fracture toughness. , This has already motivated many works focusing on the adhesion of zirconia on various metals such as Ni, Cu, or Pt . As a result, ZrO 2 could also prove to be a material of choice in low-emissivity glasses.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of this trans parent conductive stack is "dielectric/metal/dielectric" (OMO) tri pie layer. Such OMO composite multilayer stacks composed of few nanometers of Ag or Au, could exhibit much lower conductivities than the single ITO film while maintaining good optical properties (14].…”
Section: Introductionmentioning
confidence: 99%